A Comprehensive Framework for Evaluating Shelby County School District's Voluntary Preschool Program: The Challenges of Equity, Choice, Efficiency, and Social Cohesion. (June 2022) - Gulosino, Charisse; Maxwell, Phoebe
In this article, the Tennessee's Voluntary Prekindergarten (TN-VPK) program in general and the Shelby County Schools' VPK program in particular are analyzed using the policy instruments of regulation, finance, and support services. The geospatial analysis (Geographic Information Systems or "GIS") indicates that many of VPK's site locations are unable to provide access to all qualified applicants. For both TN-VPK and Shelby County Schools, it is useful not only to analyze the varied aspects of state and federally funded public-choice Pre-K programs, but also to evaluate the consequences to equity, freedom of choice, productive efficiency, and social cohesion in a geospatial context.